Construction and adapting of psychological and educational scales: basic concepts and methodological steps - BOUKRAA, Imene (Journal of Human Sciences, 2020)
The measurement of many psychological and educational variables is based on the construction of scales and tests, which make it easier for researchers to measure, for scientific or diagnostic or therapeutic purposes. The researcher can build a test or use a ladder that has already been built before, in another environment, and another culture. Given the sensitivity of the psychological and educational variables and the specificity of the concepts likely to be influenced by the social and cultural context and by the characteristics of the target sample, it is necessary for the researcher to work on the adaptation of the scales and tests, respecting the methodology of scientific research. Therefore, through this research paper, we will discuss the stages of building psychological and educational tests and scales, and conditioning, and the most important thing that must be respected about cultural transportation.